A [Fe(bpy)3]2+ grafted graphitic carbon nitride hybrid for visible light assisted oxidative coupling of benzylamines under mild reaction conditions. Issue 8 (7th January 2016) - Kumar, Arvind; Kumar, Pawan; Joshi, Chetan; Ponnada, Srikanth; Pathak, Abhishek K.; Ali, Asgar; Sreedhar, Bojja; Jain, Suman L.
Abstract : Iron(ii ) bipyridine grafted on graphitic carbon nitride (Fe(bpy)3 /npg-C3 N4 ) was found to be an efficient photocatalyst for oxidative coupling of benzyl amines using molecular oxygen as an oxidant and a household white LED as a light emitting source. Abstract : The present paper describes the use of a readily synthesized, environmentally benign, reusable and non-toxic iron based nanocomposite i.e iron(ii ) bipyridine grafted to graphitic carbon nitride (Fe(bpy)3 /npg-C3 N4 ) as a photocatalyst, molecular oxygen as an oxidant and a household white LED as a light emitting source for the oxidative coupling of benzylamines under mild reaction conditions. The developed heterogenized homogeneous photocatalyst showed excellent activity with the added benefits of facile recovery and efficient recycling ability without any significant loss in catalytic activity.